The occurrence of various types of disinfectant by-products (trihalomethanes, haloacetic acids, haloacetonitrile) in drinking water - Dubey S.; Gusain D.; Sharma Y.C.; Bux F. (My University, 2025)
Disinfection of drinking water supplies with various disinfectants has been integral for maintaining high microbial quality of drinking water. Disinfectant inactivates disease-causing organisms and effectively reduces waterborne diseases to ensure safe consumption of water. However, an unintended chemical reaction between disinfectants and naturally occurring organic and inorganic precursors or anthropogenic compounds in the source waters results in the generation of a number of disinfection by-products (DBPs) including trihalomethanes, haloacetic acids, and haloacetonitrile in drinking water. Due to potential adverse health effects (from cancer induction to birth defects, etc.) posed by these geno- and cytotoxic DBPs on exposure, they have received great concern worldwide and thus are regulated by the United States Environmental Protection Act in the water industry. The objective of this chapter is to provide an insight into the apprehension of DBP generation in drinking water, occurrence, types of DBPs, and associated adverse health effects. © 2020 Elsevier Ltd. All rights reserved.